Análise da ação de catequinas derivadas do chá verde em dentina humana erosivamente desmineralizada: estudos in vitro e in situ - Bezerra, Maria Denise Rodrigues de Moraes (2016)
The objective of this study was to evaluate and compare the action of different enzyme inhibitors on human dentin in cyclical erosion challenging situation. To this were carried out 3 projects that yielded the following chapters: In the chapter 1 and 2, coronary or root human (n=10) dentin blocks (4x4x2 mm) were submitted cyclically (3x/ day/3 days) to erosive challenge by immersion in acid [dehydrated citric acid (C6H8O7), pH 3.75, 60 s] followed by treatments depending on the group: G1-distilled water; G2- 0.12% Chlorhexidine digluconate (CHX); G3- Green tea infusion (GT). The blocks were analyzed daily by surface profilometry and hardness. In the chapter 3, a randomized, blinded, crossover, in situ study in which 20 volunteers used palatal intra oral device for three phases of 5 days each, containing 4 blocks of human dentin. They were immersed in human saliva for 2 hours to acquired pellicle formation. The erosive challenge was performed by the device immersion in 50 mL of Coke™ (pH 2.6, 4x/ day /1 min, extraorally) followed by treatment (4x/ day) by dropping on blocks 1 mL of the following solutions: G1- 0.05% Sodium fluoride, G2- 0.1% Epigallocatechin-3-gallate (EGCG), G3- Green tea infusion. At each phase the volunteer used only one substance. Quantitative analyzes were performed, such as percentage loss of surface hardness, roughness and wear, as well as qualitative analysis by scanning electron microscopy. Complementing the studies to analysis of enzyme inhibition, human dentin blocks were milled, subjected to erosion by citric acid and subjected to extraction of soluble proteins. Electrophoresis was performed and then the gel was incubated for 3 h in renaturation buffer modified according to the groups G1: without modification, G2- 0.12% chlorhexidine digluconate, G3- 0.05% NaF, G4- Green tea and G5- 0.1% EGCG. Gels were stained in a solution containing 0.025% Coomassie blue and destained with acetic acid 10% solution to verify the possible inhibitory action of the substances evaluated on the collagenolytic enzymes. Then were subjected to colorimetric enzyme inhibition test, in which the absorbance was measured. After extraction of dentin proteins, protein quantification by Bradford’s method was performed, which showed 0.15 µg soluble proteins. The results were analyzed using the Kolmogorov-Smirnov test to evaluate the normal range of results, followed by analysis of variance (ANOVA) and Tukey test, using a significance level of 5%. Results: A significant reduction in the dentin hardness loss in coronary dentin in vitro with the use of CHX and GT in comparison to the control (p <0.05). Treatment with GT significantly reduced wear and roughness of dentin in vitro (p <0.05). In relation to in vitro study on root dentin, the treatment with GT reduced the wear and roughness (p <0.05). There was no statistically significant difference between the groups regarding the loss of surface hardness of root dentin in vitro (p> 0.05). As for the in situ study, treatment with EGCG and GT reduced the loss of dentin hardness significantly (p <0.05). On the other hand, there was no significant difference in relation to wear and roughness values (p> 0.05). For zymography analysis, 0.12% CHX, green tea and 0.1% EGCG showed inhibitory action on the extracted metalloproteinases dentin and, the colorimetric assay green tea has enzimatic inhibition similar to standard inhibitor. Conclusion: Green tea solution reduces in vitro wear and roughness of coronary and root dentin erosively demineralized. The 0.1% EGCG and green tea reduce erosion damage on coronal dentin in situ and contribute to inactivate MMPs extracted dentin.